UPAYA MENGEMBANGKAN REGULASI EMOSI MELALUI LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK ROLE PLAYING PADA PESERTA DIDIK KELAS XI SMK LPI SEMARANG - Pink’a Titania; Dini Rakhmawati; MA Primaningrum Dian (CV. Denasya Smart Publisher, 2025)
The research conducted is entitled Efforts to Develop Emotional Regulation Through Group Guidance with Role Playing Techniques for Students of SMK LPI Semarang. The research on Efforts to Develop Emotional Regulation Through Group Guidance Services with Role Playing Techniques for Class XI Students of SMK LPI Semarang is motivated by the low level of emotional regulation of students as indicated by the exclusion of these students from their peers, causing students to become sensitive to suggestions and criticisms from others. The purpose of this study was to determine Efforts to Develop Emotional Regulation Through Group Guidance Services with Role Playing Techniques for Class XI Students of SMK LPI Semarang. This type of research is quantitative research using the true-experimental method with a pre-test and post-test design model. The sample in this study was 21 students who then became the experimental group and the control group. The data collection tool used the emotional regulation scale. The results of the hypothesis test obtained significance (2-tailed) <0.05 indicating a significant difference between the control group and the experimental group. Meanwhile, the t-test result of 0.0064 showed a difference in the treatment given to the experimental group compared to the control group. It can be concluded that group guidance services with role playing techniques can help develop emotional regulation of SMK LPI Semarang students. Based on the results of this study, the suggestion that can be conveyed is that group guidance services with role playing techniques can be used as one of the treatment methods to develop emotional regulation.